2022
DOI: 10.1111/1475-4932.12689
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Australian Monetary Policy in the Twenty‐First Century*

Abstract: Using the Reserve Bank of Australia's MARTIN model, we compare actual monetary policy decisions with a counterfactual in which the cash rate is set according to an optimal simple rule. We find that monetary policy played a crucial role in avoiding a potential recession in 2001 and mitigating the downturn in 2008–09. By contrast we find that the cash rate was too high during 2016–19, keeping inflation below the Reserve Bank's target band. Optimal monetary policy in 2016–19 would have involved a substantially lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…… An otherwise manageable downturn could be turned into something more serious. (Lowe 2017b) Some commentators have suggested that its concern about house prices led the RBA to keep monetary policy tighter than justified by other economic conditions, resulting in higher unemployment (Gross and Leigh 2022;Tulip 2022). Despite stating that it did not target debt or house price ratios (Lowe 2017b), the RBA in other comments suggested that both factors were influencing monetary policy:…”
Section: The Australian Governmentmentioning
confidence: 99%
“…… An otherwise manageable downturn could be turned into something more serious. (Lowe 2017b) Some commentators have suggested that its concern about house prices led the RBA to keep monetary policy tighter than justified by other economic conditions, resulting in higher unemployment (Gross and Leigh 2022;Tulip 2022). Despite stating that it did not target debt or house price ratios (Lowe 2017b), the RBA in other comments suggested that both factors were influencing monetary policy:…”
Section: The Australian Governmentmentioning
confidence: 99%
“…During the period from 2013 to 2019, there was some public discussion from time to time of the RBA being inhibited in lowering interest rates, not because it thought that unemployment was below the NAIRU but because it was concerned about the systemic risks associated with high levels of borrowing for housing and the associated housing asset boom. Gross and Leigh pick up this point in relation to their discussion of the period between 2016 and 2019: ‘the RBA was concerned about financial stability and accordingly set interest rates higher than inflation and unemployment alone would warrant’ (Gross and Leigh 2022, p. 281). They are very critical of such a policy stance.…”
Section: The Second Way In Which Things Have Gone Wrong For the Rba: ...mentioning
confidence: 99%
“…In a careful study, Isaac Gross and Andrew Leigh, using the RBA's MARTIN model, find that the interest rate was kept too high during the period from 2016 to 2019, so that during that time inflation fell below the RBA's target band (Gross and Leigh 2022). The authors did this by comparing actual monetary policy decisions to a counterfactual in which the interest rate was set according to an optimal simple rule.…”
Section: The Rba's Mistakes About the Nairumentioning
confidence: 99%
See 2 more Smart Citations